Effectiveness and efficiency of nano kaolin clay as bitumen modifier: Part A - Putra Jaya, Ramadhansyah; Haryati, Yaacob; Norhidayah, Abdul Hassan; Al-Saffar, Zaid Hazim (Elsevier, 2022)
This study is intended to deliver a better understanding on the improvements obtained through bitumen modification. By giving new ideas to the road engineers on how to manipulate the particular properties of constituent materials, it is hoped that this can increase the usage value of bitumen and its application in road construction. This project also assists engineers and researchers to choose an alternative option to improve the conventional bitumen in terms of economy, where a typical quantity of nanomaterials are normally added into binder to a lesser extent compared to other types of modifier. It is expected that this research will significantly contribute added value toward the utilization of natural minerals, such as kaolin clay, for the enhancement of the modified binder performance. Thus, the asphalt binder incorporating Nano kaolin clay (NKC) was tested and evaluated. It is hoped that NKC-modified asphalt will improve the strength and durability performance of bitumen.